Efficacy of Expired Antibiotics: A Real Debate in the Context of Repeated Drug Shortages - Benjamin Davido; Hugues Michelon; Christel Mamona; Pierre de Truchis; Karim Jaffal; Azzam Saleh-Mghir (Antibiotics, 2024)
This narrative review aims to discuss the main interest in and cautions associated with the use of expired antibiotics in the context of repeated shortages, notably in Europe. Articles concerning the topic of expiry dates related to antibiotic use were reviewed using keywords in the PubMed®/MEDLINE and Google Scholar databases to identify the most extensive evidence-based documentation. The present review evaluates the potential interest and efficacy of using expired drugs and their possible related adverse events. Overall, in the context of drug shortages, expiry dates could be safely extended for at least one year for most solid antibiotics (tablets or powder) used in daily clinical practice, as long as they are stored under the right conditions, in accordance with the summary of product characteristics.